Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security 2019
DOI: 10.1145/3319535.3363206
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Worlds

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Software-based solutions are commonly achieved through the use of Intel Transactional Synchronization Extensions (TSX) [14,49] and Oblivious RAM (ORAM) [2,43,47]. Bulck et al [57] presented an analysis of the vulnerabilities and mitigations in shielding runtimes implementations, including SGX.…”
Section: Intel Sgx Security Assessmentmentioning
confidence: 99%
“…Software-based solutions are commonly achieved through the use of Intel Transactional Synchronization Extensions (TSX) [14,49] and Oblivious RAM (ORAM) [2,43,47]. Bulck et al [57] presented an analysis of the vulnerabilities and mitigations in shielding runtimes implementations, including SGX.…”
Section: Intel Sgx Security Assessmentmentioning
confidence: 99%
“…Of course, any vulnerability in the SDK itself will automatically impact all enclaves that make use of it. In "A Tale of Two Worlds" [5] Van Bulck et al discovered multiple vulnerabilities in all open source SDKs for enclave development that they tested. This paper do not invalidate the security properties of SGX in and of itself, but it highlights the difficulty in writing secure software in general and enclaves in particular.…”
Section: Attacks On Sgxmentioning
confidence: 99%
“…The basic attack is a controlled channel attack, see sec. III-A 5. EPID or Enhanced Privacy ID is Intel's recommended algorithm used for attestation while preserving privacy of the trusted system…”
mentioning
confidence: 99%
“…Not only should the application not contain bugs, but it should be side-channel resistant. It was also shown that TEE SDKs themselves are often vulnerable to various attacks [117]. Minimizing application functionality can potentially lead to more secure applications.…”
Section: Designing Trusted Applicationsmentioning
confidence: 99%